Reconstructive Therapy of an Adenomatoid Odontogenic Tumor Associated with an Erupted Maxillary Lateral Incisor: Report of a Rare Case - Chokami Rafiei , Sahar; Jafary Nodoushan, Zahra (Galen Medical Journal, 2024)
Background: Adenomatoid odontogenic tumor is an asymptomatic, rare, benign neoplasm of odontogenic epithelium origin with a slow growth rate. Case Presentation: We describe a case of a 15-year-old male patient of Asian descent, who presented with a 0.8*0.8*0.3-cm expansile mass in the lateral incisor region, which is an uncommon location and gender for AOT. Cone-beam computed tomography revealed evidence of a well-defined unilocular radiolucent lesion in the anterior maxilla, with snowflake calcification, expansion of the buccal cortical plate, and lingual drift of the lateral incisor. After complete excision of the mass under local anesthesia and extraction of the associated tooth, the defect was filled with xenograft, covered with pedicle connective tissue graft from the palate, and sutured. Histological sections showed a benign odontogenic tumor composed of a proliferation of spindle-shaped epithelial cells forming strands and whorls structure. A thick capsule surrounded the lesion. Some basophilic calcification with concentric structures was also seen. A piece of oral mucosa covered by parakeratinized stratified squamous epithelium was evident. There was no evidence of malignancy. Conclusion: Clinical, radiographic, and histopathologic findings aided the final diagnosis of the AOT. The patient was treated surgically and later rehabilitated with a removable prosthesis. No recurrence was detected over the one-year follow-up. This study can help diagnose and manage this lesion according to its specific characteristics.